2016
DOI: 10.1111/aor.12789
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Implantation of HeartWare Assist Device and Simultaneous Tricuspid Valve Reconstruction Through Partial Upper Sternotomy

Abstract: Left ventricular assist device (LVAD) implantation is a well-established therapy to support patients with end-stage heart failure. However, the operative procedure is associated with severe trauma. Third generation LVADs like the HeartWare assist device (HeartWare, Inc., Framingham, MA, USA) are characterized by enhanced technology despite smaller size. These devices offer new minimally invasive surgical options. Tricuspid regurgitation requiring valve repair is frequent in patients with the need for mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, we expanded the indication for this minimally invasive access and increasingly use it in patients with the need for left ventricular assist device (LVAD) support or even combined procedures such as LVAD implantation and tricuspid valve repair. 12 Bentall and de Bono developed the composite aortic valve and root replacement with coronary artery reimplantation in 1968, and during the following years, the technique was modified. [17][18][19][20] Later on, valve-sparing operations 21,22 and implantation of valved conduits were used for ARR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we expanded the indication for this minimally invasive access and increasingly use it in patients with the need for left ventricular assist device (LVAD) support or even combined procedures such as LVAD implantation and tricuspid valve repair. 12 Bentall and de Bono developed the composite aortic valve and root replacement with coronary artery reimplantation in 1968, and during the following years, the technique was modified. [17][18][19][20] Later on, valve-sparing operations 21,22 and implantation of valved conduits were used for ARR.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last years, the use of minimally invasive surgical access techniques such as partial upper sternotomy (PUS) increased, as its advantages could be demonstrated in numerous clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12] Until now, minimally invasive surgical access is not routinely used in patients with the need for aortic root replacement (ARR), and full median sternotomy remains the standard operative access.…”
Section: Introductionmentioning
confidence: 99%
“…Never the less, Hillebrand et al reported 4 cases of less invasive LVAD-Implantation and concomitant TVR using Cosgrove-Edwards partial flexible annuloplasty ring for tricuspid valve regurgitation through upper hemi-sternotomy under complete CPB. The survival rate remained 100% for these patients (29). Further, Schaefer et al reported a case of successful less invasive HeartWare HVAD Implantation and simultaneous transapical transcatheter aortic valve replacement using a JenaValve (JenaValve Technologies Inc., Munich, DE) in a patient with ischemic cardiomyopathy and aortic valve regurgitation through right anterior and left anterior thoracotomies.…”
Section: Concomitant Procedures At the Time Of Less Invasive Vad Implmentioning
confidence: 99%
“…Hillebrand et al of the University Hospital of the Westfaelische Wilhelms‐University Muenster, Muenster, Germany reported on minimally invasive implantation of the HeartWare assist device and simultaneous tricuspid valve reconstruction through partial upper sternotomy. Four male patients underwent this procedure.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%